Higiene Genetalia sebagai Faktor Risiko Infeksi Menular Seksual (IMS) pada Ibu Rumah Tangga di Puskesmas Bandarharjo Semarang - Kumalasari Kumalasari; Henry Setyawan; Bagoes Widjanarko; Muchlis Achsan Udji Sofro (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : STI (Sexual Transmission Infection) resulted in sexual and reproductive health issues that affect women, especially among housewives, children and the poor. Factors that may affect the incidence of STIs covers all aspects of epidemiology: age, race, education, occupation, economic status, marital status, knowledge, attitudes and practices in the treatment of genital hygiene. PHC Bandarharjo with the incidence of STI is quite high of 50 cases in 2014 and 90% are housewives. This study aims to prove hygiene genital factors affect the incidence of STI in housewives.Methods : This study used a mixed methods where quantitative was as the main approach with case-control design. Total sample of 80 with a ratio of 1:1 (40 respondents each group), in PHC Bandarharjo. As the case is positive housewife STI and control is negative h ousewife STI after physically examined at the PHC and laboratories Bandarharjo. Data was analyzed by univariate, bivariate (chi-square) and multivariate (logistic regression), followed by in-depth-interviews.Results : The result show the factors are shown to affect the STI on the housewife is not wash the vagina before sexual intercourse (OR = 7.7; 95% CI 2.0 to 29.1; p = 0.002), vaginal douching (OR = 7, 7; 95% CI 2.0 to 29.1; p = 0.002), low family income <UMR (OR = 4.0;95% CI 1.4 to 14.3; p = 0.030).Conclusion : Risk factors influencing STIs to wards housewives are not wash the vagina before sexual intercouse, perform vaginal douching, family income <UMR